Effect of Different Levels of Diet Dilution During Finisher Period on Broiler Chickens Performance and Carcass Characteristics - Sahraei, Mahmood; Shariatmadari, Farid (International Journal of Poultry Science, 2007)
This experiment was conducted to compare the effects of diet dilution with sand and wheat bran (wt:wt) on broiler chicken performance and carcass characteristics during finisher periods from 35 to 45 ages. Hence one Completely Randomized Design (CRD) that include different levels of finisher diet diluted with sand and wheat bran (wt:wt) (in levels 7, 14, 21 or 28%) and one control group (undiluted finisher diet) in 5 treatment with four replicate each containing five male broiler chicken (total 100 birds) of arain strain. Comparing means levels of diet dilution with control birds showed that feed intake in different levels was more than control birds (p<0.01). But live weight (at 45 ages), body weight gain only in 28% levels were less than control birds (p<0.01). Carcass weight in 28 and 21% levels and abdominal fat percent in 14, 21 and 28 levels were significant difference with control birds (p<0.01). However percentage of breast and thigh at all levels of diet dilution except of 7% level were less than control birds (p<0.01).